HUBUNGAN DUKUNGAN SOSIAL DENGAN STRES SAAT PEMBELAJARAN DARING PADA MAHASISWA KEDOKTERAN UNIVERSITAS UDAYANA - A.A. Sintya Wulandari; Made Oka Ari Kamayani; Ni Luh Putu Shinta Devi (Program Studi Sarjana Ilmu Keperawatan dan Profesi Ners, Fakultas Kedokteran, Universitas Udayana, 2021)
The Covid-19 pandemic has had an impact on several sectors, one of which is the education that is in learning methods that are switched to online. The sudden change of method can certainly cause stress to some students. The stress experienced can be reduced when individuals get social support from family, friends, and significant others as needed. Social support is a form of help, attention and support that really needed by individuals when experiencing a problem. This research aims to know the relationship between social support and stress during online learning in student faculty of medicine Udayana University. This research used a descriptive correlative design with a cross sectional approach. The research sample was obtained by using probability sampling with a proportionate stratified random sampling technique with a large sample was 341 students. Spearmen Rank results of the test were obtained by the value of the Sig p 0.000 < 0.05 and the value of the r -364, which means there was a significant relationship between social support and stress during online learning in student faculty of medicine Udayana University with a negative direction and weak relationship strength. Students can be able more caring, supportive, motivating, helping each other and also need an active role from academic supervisors to always accompany and assist students in every process that will be passed together.